Application of Handheld Laser-Induced Breakdown Spectroscopy (LIBS) to Geochemical Analysis. Issue 5 (May 2016) - Connors, Brendan; Somers, Andrew; Day, David
While laser-induced breakdown spectroscopy (LIBS) has been in use for decades, only within the last two years has technology progressed to the point of enabling true handheld, self-contained instruments. Several instruments are now commercially available with a range of capabilities and features. In this paper, the SciAps Z-500 handheld LIBS instrument functionality and sub-systems are reviewed. Several assayed geochemical sample sets, including igneous rocks and soils, are investigated. Calibration data are presented for multiple elements of interest along with examples of elemental mapping in heterogeneous samples. Sample preparation and the data collection method from multiple locations and data analysis are discussed.